Optimization of a mining operation (geometalurgia) - case study – Minereicis S.A. - Salazar, Ana Milena (2018)
The mining company MINEREICIS SA located in the canton of Ponce Enríquez province of Azuay dedicated to the extraction of gold and copper bearing minerals has detected gold in the final tailings, additionally in the flotation concentrates it has a percentage of arsenic, which penalizes its commercialization. Having explained this, a research was carried out to optimize the operation from the geometallurgy. The geometallurgy characterization of the deposit, provides the information for the evaluation of resources, to define the methods of exploitation and the technique of benefit of minerals. The mineralogical characterization of the deposit was carried out by sampling methodically the veins for the formation of a composite to submit them to the metallurgical tests. All this information does not derive from the variables that geometallurgy uses for the optimization of the mining process. The hypothesis is: conducting a technical - scientific research will optimize the metallurgical process of recovery of gold and concentrate. Referential Framework: mining geology of the Bella Rica District, current status of the Benefit Plant. Theoretical Framework: parameters of the veins, comminution operations.